Vertebral Artery Injury in Cervical Spine Surgery: Results from AOSpine North America Multicenter Study on 16, 582 Patients. Issue 1 (April 2016) - Kannan, Abhishek; Mai, Harry; Hsu, Wellington; Hilibrand, Alan; Nassr, Ahmad; Arnold, Paul; Fehlings, Michael; Traynelis, Vincent; Gokaslan, Ziya; Mroz, Thomas; Bydon, Mohamad; Smith, Zachary; et al.
Introduction: Vertebral artery injury is a rare but serious complication of cervical spine surgery with an overall incidence rate of 1.4% (Rampersaud, 2006). Iatrogenic injury of the vertebral artery can lead to serious complications including lateral medullary (Wallenberg) syndrome, quadriparesis, and mortality. The high rate of vertebral artery anomalies in the general population mandates assessment via advanced imaging modalities in the preoperative period (Schroeder, 2013). The rarity of this complication makes it difficult to set expectations after an injury is encountered. This study utilized a multi-center database to compile outcomes data after vertebral artery injury during a cervical spine procedure. Materials and Methods: A multi-center retrospective case series was compiled involving 23 medical institutions. Inclusion criteria included patients who underwent cervical spine surgery between 2005–2011 and who sustained a vertebral artery injury. IRBs were obtained from all institutions and data was sent to a private research organization that collected and collated all of the data. Patients were evaluated on the basis of condition-specific functional status using the Neck Disability Index (NDI), modified Japanese Orthopaedic Association (mJOA) score, the Nurick scale, and the 36-Item Short-Form Health Survey (SF-36). Results: Vertebral artery injuries were identified in a total of 14 of 16, 582 total patients screened (8.4 per 10, 000). The mean age of patients with vertebral artery injury was 59 years (+/− 10) with a female predominance (78.6%). Diagnoses of affected patients included 7 with myelopathy, 3 with radiculopathy, 1 with cervical instability, and 2 with metastatic disease. The mean duration of operative time for cases was 4.7 hours (+/− 1.8). Vertebral artery injury was also associated with substantial blood loss (770 mL), although only 3 cases required transfusion. Of the 14 cases, 7 occurred with an anterior only approach, 3 cases with posterior only approach, and 4 during circumferential approach. Average length of hospital stay for these patients was 10 days (+/− 8). Notably, 13 of the 14 (92.86%) cases reportedly resolved without residual deficits. Compared with preoperative baseline NDI, Nurick, and SF-36 physical and mental component scores for these patients, there were no observed changes after surgery ( p  = 0.20 Ð 0.94). Conclusion: Vertebral artery injuries are potentially catastrophic complications that can be sustained from either anterior or posterior cervical spine approaches. This adverse event is associated with an increase in hospital stay and functional disability measured on NDI score. However, the data from this study suggests that with proper steps to ensure hemostasis, patients recover function at a high rate and do not exhibit residual deficits (13 out of 14). Preoperative imaging studies may provide insight into VA anomalies and anatomic variations and are vital to the preoperative assessment. Furthermore, although surgeons should expect increased blood loss once a vertebral artery injury is encountered, patients do not often require a blood transfusion.